Answer :

isyllus

Answer:

Correct answer:

A. I and II

Step-by-step explanation:

First of all, let us have a look at the steps of finding inverse of a function.

1. Replace y with x and x with y.

2. Solve for y.

3. Replace y with [tex]f^{-1}(x)[/tex]

Given that:

[tex]I.\ y=x \\II.\ y=\dfrac{1}x \\III.\ y=x^2 \\IV.\ y=x^3[/tex]

Now, let us find inverse of each option one by one.

I. y = x, a(x) = x

Replacing y with and x with y:

x = y

x = [tex]a^{-1}(x)[/tex] = [tex]a(x)[/tex]  Hence, I is true.

II. [tex]y =\dfrac{1}{x}[/tex]

Replacing y with and x with y:

[tex]x =\dfrac{1}{y}[/tex]

[tex]x=\dfrac{1}{a^{-1}(x)}[/tex]

[tex]\Rightarrow a^{-1}(x) = \dfrac{1}{x}[/tex]

[tex]a^{-1}(x)[/tex] = [tex]a(x)[/tex]  Hence, II is true.

III. [tex]y =x^{2}[/tex]

Replacing y with and x with y:

[tex]x =y^{2}\\\Rightarrow y = \sqrt x\\\Rightarrow a^{-1}(x) = \sqrt{x} \ne a(x)[/tex]

 Hence, III is not true.

IV. [tex]y =x^{3}[/tex]

Replacing y with and x with y:

[tex]x =y^{3}\\\Rightarrow y = \sqrt[3] x\\\Rightarrow a^{-1}(x) = \sqrt[3]{x} \ne a(x)[/tex]

Hence, IV is not true.

Correct answer:

A. I and II

Other Questions